The secret of the point and click adventures - Vraneševič, Goran (Teorija in praksa, 2014)
This article analyzes the general characteristic of once exceptionally popular genre of adventure video games, which reached its peak with the famous pirate series Monkey Island. Although there have been various attempts to revive it, it is inevitably situated among the relics of history. The reason could be traced to a variety of developmental, economic and conceptual features, but in the final instance it was its own structure that led to its downfall or death. Since its formation, the adventure genre was namely imbued with an unabolishable contradiction, which certainly situates it alongside psychoanalytic practice. It was simultaneously striving for something too much and too little. The adventure games are on the one hand based on the assumption that all the in-game possibilities are pre-arranged, so that the player is only left to acknowledge and approve the already adopted path. But on the other, the genre thrived on experimenting with the game mechanism, where the contingent acts of pointing retroactively undermined the necessity of such preconditioned actions. The article is accordingly based on the premise that the ensuing inference doesn't solely indicate a specific feature of this genre, but also highlights the peculiarity of human existence as such.
Keywords: Cultural studies; Kulturne študije; meaning; pomen; Psihoanaliza; Psychoanalysis; Video games; Videoigre